Relationship of Structure and Biological Activity of Monosaccharide Lipid A Analogues to Induction of Nitric Oxide Production by Murine Macrophage RAW264.7 Cells - Funatogawa, Keiji (American Society for Microbiology, 1998)
Lipid A is the active center of bacterial lipopolysaccharide (LPS), which exhibits diverse biological activities via the production of various mediators. We investigated the production of nitric oxide (NO), one of the mediators, by a murine macrophage cell line, RAW264.7, upon stimulation with a series of monosaccharide lipid A analogues to elucidate the relationship of structure and activity in NO production. The production of other representative mediators, such as tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6), was also investigated to compare the structural requirements for the production of these cytokines with those for the production of NO. Structure-activity relationships in NO production correlated well with those in the production of TNF-α and IL-6. Among the lipid A analogues possessing different numbers of acyl groups on a 4-O-phosphono-d-glucosamine backbone, compounds like GLA-60 that possess three tetradecanoyl (C(14)) groups exhibited stronger activities in the production of the mediators than compounds possessing four or two C(14) groups. Time course study of the production of these mediators showed that production of NO started and peaked later than those of TNF-α and IL-6. Neither neutralization of TNF-α activity by antibody nor suppression of TNF-α production by pentoxifylline showed a significant suppressive effect on production of NO and IL-6 upon stimulation with LPS or lipid A analogues. Neutralization of IL-6 activity by antibody showed no significant suppressive effect on production of NO and TNF-α. A monosaccharide lipid A analogue (GLA-58) which exhibited no detectable agonistic activity showed a suppressive effect on the production of all three mediators upon stimulation with LPS or lipid A analogues. These results indicate that signals for NO production by LPS agonists in murine macrophages are transduced in good correlation with those for production of TNF-α and IL-6, although they are not transduced via production of those cytokines.